METONYMISATION OF MEDICAL EPONYMS BASED ON PERSONAL NAMES AND THEIR METONYMIC PATTERNS IN ENGLISH CLINICAL TERMINOLOGY - STEHNITSKA, Liubov; KIYKO, Svitlana; KYRYCHENKO, Oksana (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Metonymisation of Medical Eponyms Based on Personal Names and Their Metonymic Patterns in English Clinical Terminology. This paper presents insights into the metonymisation of medical eponyms based on a comprehensive overview of relevant literature. The article introduces a corpus-based study that analyses 25,787 medical eponyms derived from proper names extracted from articles, dictionaries, and specialised online resources. Given the established metonymic frameworks, this research investigates the characteristics of medical eponyms categorised as metonymic expressions through descriptive analysis. In our study, we considered eponymy as a subclass of metonymy, involving metonymic shifts where a name indirectly refers to a related medical concept. The specific features of a medical phenomenon are transferred from the object to a person who either discovered or is somehow associated with it. In this case, the proper name in an eponymous term does not provide access to biographical information but reveals the meaning of the medical phenomenon associated with a person. We also regard eponymy as a common form of metonymy that manifests in elliptic constructions, where the proper name is used without common nouns like disease, reflex, sign, etc. Metonymy is also considered from a cognitive standpoint in medical terminology, as it is used in reasoning to indicate how humans perceive medical objects. The information contained in eponyms gradually accumulates in the doctor's mind. Such knowledge accumulation helps to elucidate the relationship between language and medicine, enriching not only theoretical linguistics but also medical practice and education. The deeper the knowledge, the more information is condensed within the eponymous term; i.e., the meaning of a medical eponym is revealed as it is studied and characterized by individual associative layers and identification descriptors, where the proper name serves as a trigger for understanding the information ingrained within it. The proper name picks out a unique entity from several similar ones and provides access to some specific information. A mental lexicon uses such names as a compact container for keeping a large amount of information that can be grained into particular categories. Such metonymic categories as PHYSICIAN FOR THE DISEASE, PATIENT FOR THE DISEASE, and PART-FOR-WHOLE METONYMY can be specified within medical terminology due to the associative relations between source and target. Such an associative relationship between eponyms and medical phenomena is based on knowledge and experience, which steadily extend and may convey complex concepts quickly. The cognitive framework of metonymy facilitates the structuring of conscious processes and potentially influences standardized medical nomenclature, which in turn enhances clarity in international communication. REZUMAT. Metonimizarea eponimelor medicale bazate pe nume personale și modelele lor metonimice în terminologia clinică engleză. Acest articol prezintă perspective asupra metonimizării eponimelor medicale pe baza unei analize cuprinzătoare a literaturii relevante. Articolul introduce un studiu bazat pe corpus care analizează 25.787 de eponime medicale derivate din nume proprii extrase din articole, dicționare și resurse online specializate. Având în vedere cadrele metonimice stabilite, această cercetare investighează caracteristicile eponimelor medicale clasificate ca expresii metonimice prin intermediul unei analize descriptive. În studiul nostru, am considerat eponimia ca o subclasă a metonimiei, implicând schimbări metonimice în care un nume se referă indirect la un concept medical conex. Caracteristicile specifice ale unui fenomen medical sunt transferate de la obiect la o persoană care la descoperit sau care este asociată în vreun fel cu acesta. În acest caz, numele propriu dintr-un termen eponim nu oferă acces la informații biografice, ci dezvăluie semnificația fenomenului medical asociat cu o persoană. De asemenea, considerăm eponimia ca o formă comună de metonimie care se manifestă în construcții eliptice, în care numele propriu este utilizat fără substantive comune precum boală, reflex, semn etc. Metonimia este, de asemenea, considerată din punct de vedere cognitiv în terminologia medicală, deoarece este utilizată în raționament pentru a indica modul în care oamenii percep obiectele medicale. Informațiile conținute în eponime se acumulează treptat în mintea medicului. Această acumulare de cunoștințe ajută la elucidarea relației dintre limbă și medicină, îmbogățind nu numai lingvistica teoretică, ci și practica și educația medicală. Cu cât cunoștințele sunt mai aprofundate, cu atât mai multe informații sunt condensate în termenul eponim; adică, semnificația unui eponim medical este revelată pe măsură ce este studiat și caracterizat prin straturi asociative individuale și descriptori de identificare, unde numele propriu servește ca un declanșator pentru înțelegerea informațiilor înrădăcinate în el. Numele propriu selectează o entitate unică dintre mai multe entități similare și oferă acces la anumite informații specifice. Un lexic mental utilizează astfel de nume ca un container compact pentru păstrarea unei cantități mari de informații care pot fi împărțite în categorii specifice. Categorii metonimice precum MEDIC PENTRU BOALĂ, PACIENT PENTRU BOALĂ și METONIMIE PARTE-PENTRU-ÎNTREG pot fi specificate în terminologia medicală datorită relațiilor asociative dintre sursă și țintă. O astfel de relație asociativă între eponime și fenomene medicale se bazează pe cunoștințele și experiența utilizatorului, care se extind constant și pot transmite rapid concepte complexe. Natura cognitivă a metonimiei facilitează structurarea gândirii și raționamentului uman și poate influența nomenclatura medicală standardizată, ceea ce, la rândul său, sporește claritatea în comunicarea internațională. Cuvinte-cheie: metonimie, termeni eponimi, eponim, nume proprii, modele metonimice. Article history: Received 15 January 2025; Revised 04 July 2025; Accepted 12 August 2025; Available online 24 September 2025; Available print 30 September 2025